2021
DOI: 10.1038/s41467-021-20904-2
|View full text |Cite
|
Sign up to set email alerts
|

NUPR1 is a critical repressor of ferroptosis

Abstract: Ferroptosis is a type of iron-dependent regulated cell death, representing an emerging disease-modulatory mechanism. Transcription factors play multiple roles in ferroptosis, although the key regulator for ferroptosis in iron metabolism remains elusive. Using NanoString technology, we identify NUPR1, a stress-inducible transcription factor, as a driver of ferroptosis resistance. Mechanistically, NUPR1-mediated LCN2 expression blocks ferroptotic cell death through diminishing iron accumulation and subsequent ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
125
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(125 citation statements)
references
References 81 publications
(104 reference statements)
0
125
0
Order By: Relevance
“…Further identification of the metabolic sensors responsible for lipid synthesis, oxidation, and degradation will be important to understand the utility of ferroptosis for cancer therapy. Because glucose and lipid metabolism crosstalk at multiple levels (Chen et al, 2019;Saltiel and Kahn, 2001), it will be important to characterize how the metabolic flexibility of cancer cells may modulate ferroptotic responses in pancreatic tumorigenesis and therapy (Badgley et al, 2020;Dai et al, 2020a, Dai et al, 2020bKuang et al, 2021;Liu et al, 2021). Because ferroptosis is a type of autophagy-dependent cell death (Liu et al, 2020;Zhou et al, 2020), it is also important to understand how dysfunctional degradation pathways affect the protein levels of key metabolic regulators during ferroptosis (Chen et al, 2021c;Hou et al, 2016;Hu et al, 2021;Li et al, 2021).…”
Section: Cell Reportsmentioning
confidence: 99%
“…Further identification of the metabolic sensors responsible for lipid synthesis, oxidation, and degradation will be important to understand the utility of ferroptosis for cancer therapy. Because glucose and lipid metabolism crosstalk at multiple levels (Chen et al, 2019;Saltiel and Kahn, 2001), it will be important to characterize how the metabolic flexibility of cancer cells may modulate ferroptotic responses in pancreatic tumorigenesis and therapy (Badgley et al, 2020;Dai et al, 2020a, Dai et al, 2020bKuang et al, 2021;Liu et al, 2021). Because ferroptosis is a type of autophagy-dependent cell death (Liu et al, 2020;Zhou et al, 2020), it is also important to understand how dysfunctional degradation pathways affect the protein levels of key metabolic regulators during ferroptosis (Chen et al, 2021c;Hou et al, 2016;Hu et al, 2021;Li et al, 2021).…”
Section: Cell Reportsmentioning
confidence: 99%
“…In this study, we selected two genes related to iron metabolism, FPN and LCN2, as target genes. The functions of both FPN and LCN2 in cells are related to the efflux of iron ions [43][44][45][46][47][48] . In our previous study, we found the expression of the two genes were significant up-regulated when cells were treated with FeNP 36 .…”
Section: Resultsmentioning
confidence: 99%
“…In the body, Fe2+ can be transformed to Fe3+ by ceruloplasmin, resulting in the combination of Fe3+ with transferrin (TF) as a complex endocytosed through membrane protein TF receptor 1 (TFR1) Zheng and Conrad, 2020). Intracellular Fe3+ is reduced to Fe2+, either used to compose iron-dependent enzymes (Anderson and Vulpe, 2009) or stored in the labile iron pool (LIP) and ferritin (Bogdan et al, 2016), and the redundancy exported by ferroportin 1 (FPN1), multi-copper ferroxidase (e.g., ceruloplasmin) and ion transporter, lipocalin 2 (LCN2) (Bogdan et al, 2016;Anderson and Frazer, 2017;Liu J. et al, 2021). Ultimately, the increased iron released to the LIP by ferritin-targeted autophagy, depletion of ferritin or some other circumstances is the essential condition for ferroptosis, just like a wizard's wand, waiting for a killing curse to taste death (Figure 2).…”
Section: Labile Iron Pool-powerful Strength Of the Elder Wandmentioning
confidence: 99%
“…Ferroptosis can be obstructed by iron chelators (Friedmann Angeli et al, 2014), knockdown of TFR1 (Gao et al, 2015;Torii et al, 2016) (identified as a ferroptosis marker) (Feng et al, 2020) and eliminating autophagy-related genes or the selective cargo receptor nuclear receptor coactivator 4 (NCOA4) for blocking ferritinophagy (Gao et al, 2016;Zheng and Conrad, 2020). The stress response gene, transcriptional regulator (NUPR1), targeted LCN2 as an effector gene to inhibit iron-dependent ferroptosis and LCN2 can retard acute pancreatitis by lowering the iron level in the cytoplasm (Liu J. et al, 2021), which help us draw inspiration from this pathway to explore the relationship between iron metabolism and ferroptosis on the gene level. Lately, an unanticipated axis of ATM (Ataxia-Telangiectasia)-MTF1 (metal-regulatory transcription factor 1)-Ferritin/FPN1 contributed to lessen labile iron via inhibiting ATM, which was detected by P. H. Chen et al, discovering a new dimension in ferroptosis through kinome screen (Chen P. H. et al, 2020).…”
Section: Labile Iron Pool-powerful Strength Of the Elder Wandmentioning
confidence: 99%